Business Sustainability Pada UMKM di Banyumas: Peran Environmental Consciousness dan Green Intellectual Capital - Aziz, Muhammad Minanul; Pratama, Bima Cinintya; Pramono, Hadi; Pramurindra, Rezky (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study was to determine the role of environmental consciousness and green intellectual capital on business sustainability in MSMEs. The sampling technique used was stratified random sampling with the characteristics of MSMEs that have been operating for one year and have more than two employees. The population is known to be more than 89,000 MSMEs in Banyumas which was then calculated for sample adequacy using g*power software. From the sample calculation, this study distributed 200 samples with the number of samples that could be used as many as 198 samples. This study uses SEM (Structural Equation Modeling) analysis on SmartPLS3 software by testing two models, namely the outer model and the inner model. The results of this study indicate that environmental consciousness has a positive and significant effect on green intellectual capital (GIC). Then, GIC also has a positive and significant effect on business sustainability. Meanwhile, the GIC variable is able to mediate the relationship between environmental consciousness and business sustainability positively and significantly.